KORELASI ANTARA KETERAMPILAN DENGAN KARAKTER BERFIKIR KRITIS DAN HASIL BELAJAR FISIKA SISWA DALAM PEMBELAJARAN BERBASIS PROBLEM BASED LEARNING (PBL) KELAS X SMAN 5 PADANG - Sri Nicki Yulia (Universitas Negeri Padang, 2014)
Low of student`s learning outcomes in physics subject predicted due to the underdevelopment of its critical thinking skills. So, it needed some effort to develop critical thinking skill by applying the deemed appropriate strategy to develop the ability to critical thinking by adopt a strategy of Problem Based Learning (PBL). The purpose of this research is to investigate the relationship between critical thinking skills with the characters in the PBL-based learning in class X SMAN 5 Padang, and relationship between the character of critical thinking to student learning result in PBL-based learning in class X SMAN 5 Padang. Type of this research is